BIOFILM FORMATION AND ANTIMICROBIAL RESISTANCE OF ESCHERICHIA COLI IN VITRO TOWARDS CEFTRIAXONE AND CEFIXIME - Jihan Kalishah; Dominicus Husada; M Vitanata Arfijanto; Agung Dwi Wahyu Widodo (Current Internal Medicine Research and Practice Surabaya Journal, 2022)
Introduction: Escherichia coli is a Gram-negative bacteria and a most cause of nosocomial infections. Bacteria has the ability to form biofilm that may cause antimicrobe resistance. This biofilm protects the microbes from environmental conditions which make it the most cause of nosocomial infections including urinary tract infection and the infections resulted from the use of medical instruments. The aim of this experiment is to observe the presence of cefotaxime and ceftriaxone antimicrobial resistance in E. coli as a cause of biofilm formation. Method: This study conducted three experiments of E. coli sensitivity test on cefotaxime and ceftriaxone, E. coli resistance test after a 48 hours incubation, and optical density measurement using iMark™ ELISA Microplate Reader. Result: The results of sensitivity experiment with antibiotic cefotaxime and ceftriaxone disk showed sensitive result in wild-type E. coli and E. coli ATCC while after 48 hours incubation E. coli ATCC remains sensitive and in wild-type E. coli result are three intermediates, one sensitive and other than that it’s all change to resistance. The third experiment results were obtained from ELISA then classified into three categories. In E. coli ATCC 1 and 2, the results are mostly in high category (OD >0.240). The OD in E. coli 1 is mostly high, while results from E. coli 2 consists of one bacterium in weak category (OD <0.120), four in moderate category (OD 1.20 – 0.240), and three in high category. Conclusion: It can be concluded that E. coli resistance test in cefotaxime and ceftriaxone after 48 hours’ incubation are mostly resistant in wild-type E. coli but sensitive in E. coli ATCC.